Calcium sulfate antibiotic‐impregnated bead implantation for deep surgical site infection associated with orthopedic surgery in small animals. Issue 4 (25th January 2021) - Peterson, Lindsay C.; Kim, Stanley E.; Lewis, Daniel D.; Johnson, Matthew D.; Ferrigno, Cassio R. A.
Abstract: Objective: To report the outcomes and complications associated with antibiotic‐impregnated calcium sulfate beads for prevention and treatment of orthopedic‐related surgical site infection (SSI) in companion animals. Study design: Retrospective case series. Animals: Client‐owned cats (n = 2) and dogs (n = 14). Methods: Medical records of 16 cases in which implantation of antibiotic‐impregnated calcium sulfate beads was performed for the prevention or treatment of SSI were reviewed. Information collected included signalment, prior surgery, reason for bead placement, antibiotics used, bacterial culture results, and clinical outcomes. Results: Surgical site infection resolved in six of 10 animals treated therapeutically and did not occur in six of six animals treated prophylactically. Susceptibility of the causative bacteria to the antibiotic implanted was confirmed in five of six cases with resolved SSI treated therapeutically but in only one of four cases with unresolved SSI treated therapeutically. Complications directly related to bead placement were evident in only one case in which beads extruded from external skeletal fixator pin tracts 7 days after implantation. At final follow‐up, 11 of 12 animals without SSI had satisfactory limb use and no clinical, cytologic, or radiographic evidence of infection. Conclusion: Implantation was well tolerated. Resolution of SSI was inconsistent; however, when bacteria were susceptible to the antibiotic implanted, SSI resolved in all but one case. Clinical significance: Antibiotic‐impregnated calcium sulfate beads could be considered for prevention or treatment of orthopedic SSI in small animals. A prospective clinical study is required to obtain additional information, including the value of preoperative bacterial culture.